146.4 W end-pumped Ho : YAG slab laser with two crystals. (September 2018) - Duan, X.M.; Shen, Y.J.; Yao, B.Q.; Wang, Y.Z.
Abstract: We report a high-power two-crystal Ho : YAG slab laser. A maximum cw output power of 146.4 W at a wavelength of 2090.7 nm is achieved, corresponding to a slope efficiency of 66.0% and an optical efficiency of 61.2%. The beam quality factor is measured to be M 2 < 2.2 at different output power levels. With an acousto-optic Q -switch, a maximum average output power of 141.3, 137.7 and 134.5 W are obtained at pulse repetition rates of 20, 30 and 50 kHz, respectively. Minimum pulse widths of 39 ns, 44 ns and 74 ns are achieved for the above pulse repetition rates.